Emission characteristics of bi-fuel motorcycle - Abdul Majid, Zulkifli; Yaacob, Zulkefli; King, Martin Philip Ik Pau; Yahya, Mohd Adnan; Abd. Razak, Mohd. Masri (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Motor vehicles generate three major pollutants: Hydrocarbons (HC), nitrogen oxides (NOx), and carbon monoxide (CO). Hydrocarbon reacts with nitrogen oxides in the presence of sunlight to form ground-level ozone (smog). Nitrogen oxides contributes to the formation of acid rain while carbon monoxide can impair mental functions and is deadly in high concentrations. Statistics in Malaysia show that from 8.9 million motor vehicles registered in 1998, approximately 2 millions tones of carbon monoxide, 237 000 tonnes of oxides of nitrogen, 111 000 tonnes of hydrocarbons, 38 000 tonnes sulphur dioxide and 17 000 tonnes particulate matters were emitted into the atmosphere. Concurrent with the increasing awareness of the impact of vehicular emissions on the global environmental quality, the industry concerned has invented many new technologies on reducing the emission level. These include catalytic converters, reformulated fuels and natural gas vehicle. Malaysia is promoting the use of cleaner fuel (natural gas) in power vehicle. Combustion from natural gas produces cleaner emissions, and thus providing the inhabitants of city centers a cleaner environment. The first project in Malaysia that utilized natural gas for motorcycle was carried out by the Gas Technology Center (GASTEG) NGV Research Group from Universiti Teknologi Malaysia. This project is directed towards the study on the performance and exhaust emission of motorcycles using natural gas and gasoline. In this paper the emission characteristics of exhaust gases from the combustion of both natural gas and gasoline will be discussed. The major difference between the two fuels is that the exhaust emission from natural gas give a complete combustion, which decrease 99.6% of carbon monoxide, 72.5% of unburned hydrocarbon and eliminate nitrogen oxide emission at a speed of 70 km/hr.